2023
DOI: 10.1177/15353702231209411
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression quantitative trait loci by SVA retrotransposons within the major histocompatibility complex

Jerzy K Kulski,
Abigail L Pfaff,
Luke D Marney
et al.

Abstract: Genomic and transcriptomic studies of expression quantitative trait loci (eQTL) revealed that SINE-VNTR-Alu (SVA) retrotransposon insertion polymorphisms (RIPs) within human genomes markedly affect the co-expression of many coding and noncoding genes by coordinated regulatory processes. This study examined the polymorphic SVA modulation of gene co-expression within the major histocompatibility complex (MHC) genomic region where more than 160 coding genes are involved in innate and adaptive immunity. We charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…A recent large-scale GWAS conducted by Van Rheenen et al has identified the HLA region as a locus significantly associated with ALS, further highlighting the importance of this locus [31]. Previous studies within our group have highlighted the capability of SVAs to modulate HLA gene expression; analysis of whole genome sequencing and transcriptomic data obtained from the whole blood of individuals within the PPMI cohort discovered that SVA_24, SVA_25 and SVA_27 modulate the expression of HLA-A, HLA-B and HLA-C, and HLA-DRB1 and HLA-DRB5, respectively [33,51]. This suggests that the modulation of HLA genes by SVAs could be a common mechanism within neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 88%
“…A recent large-scale GWAS conducted by Van Rheenen et al has identified the HLA region as a locus significantly associated with ALS, further highlighting the importance of this locus [31]. Previous studies within our group have highlighted the capability of SVAs to modulate HLA gene expression; analysis of whole genome sequencing and transcriptomic data obtained from the whole blood of individuals within the PPMI cohort discovered that SVA_24, SVA_25 and SVA_27 modulate the expression of HLA-A, HLA-B and HLA-C, and HLA-DRB1 and HLA-DRB5, respectively [33,51]. This suggests that the modulation of HLA genes by SVAs could be a common mechanism within neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 88%
“…The eQTL SVA transcripts expressed at eight MHC loci ( NR_SVA_377, R_SVA_24, R_SVA_25, R_SVA_26, NR_SVA_380, R_SVA_27, R_SVA_85, NR_SVA_381 ) that are shown in Figure 1 had statistically inferred regulatory effects on classical class I and class II gene transcription levels and their different isoforms ( 44 ). The MHC SVA genotype frequencies and their influence on classical class I and class II HLA genes and transcripts based on a previous study ( 44 ) are shown in Supplementary Table 5 . The number and percentage frequency of the 64 SVA-phased haplotypes with the eight MHC genotyped SVA as present or absent insertions in the present study are shown in Supplementary Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Regulatory effects of SVA on HLA transcription levels were inferred statistically by eQTL analysis using the Matrix eQTL software ( 49 ) and described previously ( 44 ). Fastq files of whole-blood RNAseq were downloaded from the PPMI database and the referenced SVA (R_SVA) and non-referenced SVA (NR_SVA) ( Figure 1 ) were located, genotyped and identified within or outside the MHC genomic region with the assistance of the software tools, Delly2 structural variant caller and the transcript counters Salmon and DESeq2 , as previously described ( 41 , 44 ). All the transcripts’ of 1521 individuals downloaded as PPMI blood RNAseq.bam files were used to identify the genotypes of ten classical class I and class II HLA genes using the arcasHLA software tool described by Orenbach et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations